2014
DOI: 10.1038/srep06961
|View full text |Cite
|
Sign up to set email alerts
|

Electricity-driven metabolic shift through direct electron uptake by electroactive heterotroph Clostridiumpasteurianum

Abstract: Although microbes directly accepting electrons from a cathode have been applied for CO2 reduction to produce multicarbon-compounds, a high electron demand and low product concentration are critical limitations. Alternatively, the utilization of electrons as a co-reducing power during fermentation has been attempted, but there must be exogenous mediators due to the lack of an electroactive heterotroph. Here, we show that Clostridium pasteurianum DSM 525 simultaneously utilizes both cathode and substrate as elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
170
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(184 citation statements)
references
References 36 publications
9
170
5
Order By: Relevance
“…In addition, while working with Geobacter sulfurreducens, it was observed that the fermentation pattern, as well as the microbial population could be influenced by EFs. A similar observation was made with C. pasteurianum that showed 21% shift in NADH-consumption to produce PDO using glycerol as substrate [79]. Such study increases the possibilities of efficient production of electron dense compounds using small quantities of electricity.…”
Section: 3-propanediolsupporting
confidence: 78%
See 3 more Smart Citations
“…In addition, while working with Geobacter sulfurreducens, it was observed that the fermentation pattern, as well as the microbial population could be influenced by EFs. A similar observation was made with C. pasteurianum that showed 21% shift in NADH-consumption to produce PDO using glycerol as substrate [79]. Such study increases the possibilities of efficient production of electron dense compounds using small quantities of electricity.…”
Section: 3-propanediolsupporting
confidence: 78%
“…There are plenty of microbes possessing the ability to bioconvert glycerol into PDO. The recent advancements in cathodic EFs have led to enhanced PDO yield with the following advantages: (i) direct electron dissipation into PDO synthesis; (ii) selection of bacterial population adapted to reduced condition; and (iii) enhancing PDO generation as a sole NADH dissipating pathway [79]. Few studies have been performed on mixed culture glycerol EF using the strong negative potential of −1.14 V to achieve PDO production of 0.50 mol/mol glycerol, which is 2-fold higher than batch fermentation [80,81].…”
Section: 3-propanediolmentioning
confidence: 99%
See 2 more Smart Citations
“…Both products present NADH sinks (see Figure 24) and therefore one could speculate that cathodic electron feed results in an increase of cellular NADH levels as seen for C. pasteurianum. 298 However, Therefore, all three mediators should provide electrons at a potential low enough to feed into the cellular NADH pool (around -280 mV required, refer to the discussion in section 4.1.5). As discussed above the redox-pools of C. autoethanogenum depend on ferredoxin, H 2 , NADH and NADPH.…”
mentioning
confidence: 99%